A Techno-Economic Evaluation of Green Hydrogen Production in Egypt - Elsaeed, Helmy (AUC Knowledge Fountain, 2026)
The global transition toward low-carbon energy systems has heightened interest in green hydrogen as a strategic energy carrier capable of facilitating deep decarbonization across sectors that are challenging to reduce carbon emissions. Among potential producer regions, Egypt has emerged as a high-potential candidate due to its exceptional solar and wind resources, strategic geographic location, and growing policy commitment to hydrogen development. This thesis presents a comprehensive techno-economic assessment of green hydrogen production in Egypt, with a specific focus on cost competitiveness, financing conditions, and export-oriented market positioning. The analysis synthesizes existing literature to evaluate the capital expenditure (CAPEX), operational expenditure (OPEX), and resulting Levelized Cost of Hydrogen (LCOH) for large-scale renewable-based electrolysis systems. A harmonized methodology is applied to derive Egypt-specific cost benchmarks, indicating an indicative LCOH of approximately USD 3.95/kg under literature-consistent assumptions for photovoltaic-dominant and hybrid renewable configurations. It also was able to derive an approximate OPEX value. Sensitivity analysis demonstrates that CAPEX uncertainty and system utilization closely associated with renewable capacity factors and electrolyzer operating hours are the primary drivers of hydrogen cost variability, while electricity prices and financing assumptions exert secondary but still substantial influence. Beyond production economics, the thesis contextualizes Egypt’s hydrogen potential within a broader global market framework, emphasizing the significance of logistics, certification readiness, and delivered-cost competitiveness for export markets, particularly Europe. While Egypt enjoys substantial comparative advantages, including proximity to major trade routes and port infrastructure, challenges related to financing costs, infrastructure scale-up, and regulatory maturity persist. Overall, the findings indicate that Egypt can attain internationally competitive green hydrogen production, contingent upon the concurrent advancement of renewable expansion, investment de-risking, and export-oriented policy framework.